2008
DOI: 10.1186/1472-6963-8-232
|View full text |Cite
|
Sign up to set email alerts
|

Are German patients burdened by the practice charge for physician visits ('Praxisgebuehr')? A cross sectional analysis of socio-economic and health related factors

Abstract: Background: In 2004, a practice charge for physician visits ('Praxisgebuehr') was implemented in the German health care system, mainly in order to reduce expenditures of sickness funds by reducing outpatient physician visits. In the statutory sickness funds, all adults now have to pay € 10 at their first physician visit in each 3 month period, except for vaccinations and preventive services. This study looks at the effect of this new patient fee on delaying or avoiding physician visits, with a special emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…Dental health is the sector of German health care where supplementary payment in outpatient care is practised most extensively. A recent study has shown that this will keep patients not only from choosing good quality care, but also from going to the doctor at all (43), then utilization behaviour may be more pain-driven than motivated by prevention. Finally, education-related gradients are pointing to a lack of knowledge about dental hygiene and how to put it into action.…”
Section: Discussionmentioning
confidence: 99%
“…Dental health is the sector of German health care where supplementary payment in outpatient care is practised most extensively. A recent study has shown that this will keep patients not only from choosing good quality care, but also from going to the doctor at all (43), then utilization behaviour may be more pain-driven than motivated by prevention. Finally, education-related gradients are pointing to a lack of knowledge about dental hygiene and how to put it into action.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of the specific reform have abstracted from potentially heterogeneous treatment effects (Augurzky et al. ; Schreyögg and Grabka, ). Farbmacher and Winter () address measurement problems and nonlinearities that arise when using survey data to study the effects of a quarterly co‐payment, but restrict the analysis to homogeneous effects.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Heyden et al (2003) approve the positive relation between income and specialist care utilization in Belgium based on the Belgian Health Interview Survey of 1997. In addition to this, it has been pointed out that low income groups tend to avoid or delay physician visits more often than high income groups (Burström 1990;Mielck et al 2009;Rückert et al 2008).…”
Section: Introductionmentioning
confidence: 99%